Effect of Mobile Learning toward the Effectiveness of Mathematics Learning for Fourth-Grade Students in the Net Generation Era - Wahyu Ramdani; Dwijoko Purbohadi; Aprilia Kurnianti (Universitas Muhammadiyah Yogyakarta, 2022)
The net generation is born simultaneously as new technologies are being developed, exposing them to those technologies from infancy. The constant coexistence with technology in their early lives imparts technological literacy to the fictional characters. Smartphones, for example, are an inseparable part of today’s children, and this generation is not only familiar with them but also proficient at utilizing them. Most children solely use their phones for media consumption. In particular, the mathematical abilities of this generation stand to benefit from the widespread adoption and proper use of smartphones. Students at all educational levels, from elementary school on up, now view mathematics as a formidable foe. There has to be a breakthrough that utilizes emerging technology, specifically mobile learning, to put an end to this terrifying phenomenon in learning mathematics. Therefore, this study was carried out to demonstrate the effectiveness of mobile learning in teaching mathematics to fourth-grade students (9-10 years old) in this net generation era. This research was conducted to provide educators and education administrators with a point of departure for creating new approaches that better reflect the traits of that generation. One of the hoped-for outcomes of this study is an improvement in individuals’ capabilities.